A new pressure ulcer conceptual framework. (31st March 2014) - Coleman, Susanne; Nixon, Jane; Keen, Justin; Wilson, Lyn; McGinnis, Elizabeth; Dealey, Carol; Stubbs, Nikki; Farrin, Amanda; Dowding, Dawn; Schols, Jos M.G.A.; Cuddigan, Janet; Berlowitz, Dan; et al.
Abstract Aim This paper discusses the critical determinants of pressure ulcer development and proposes a new pressure ulcer conceptual framework. Background Recent work to develop and validate a new evidence‐based pressure ulcer risk assessment framework was undertaken. This formed part of a Pressure UlceR Programme Of reSEarch (RP‐PG‐0407‐10056), funded by the National Institute for Health Research. The foundation for the risk assessment component incorporated a systematic review and a consensus study that highlighted the need to propose a new conceptual framework. Design Discussion Paper. Data Sources The new conceptual framework links evidence from biomechanical, physiological and epidemiological evidence, through use of data from a systematic review (search conducted March 2010), a consensus study (conducted December 2010–2011) and an international expert group meeting (conducted December 2011). Implications for Nursing A new pressure ulcer conceptual framework incorporating key physiological and biomechanical components and their impact on internal strains, stresses and damage thresholds is proposed. Direct and key indirect causal factors suggested in a theoretical causal pathway are mapped to the physiological and biomechanical components of the framework. The new proposed conceptual framework provides the basis for understanding the critical determinants of pressure ulcer development and has the potential to influence risk assessment guidance and practice. It could also be used to underpin future research to explore the role of individual risk factors conceptually and operationally. Conclusion By integrating existing knowledge from epidemiological, physiological and biomechanical evidence, a theoretical causal pathway and new conceptual framework are proposed with potential implications for practice and research.